Pengembangan Kelas Belajar Di Mana Saja (LECAS) Platform Untuk Pendidikan Akuntansi - Akhmad Suyono; Purba Andy Wijaya; Andri Eko Prabowo; Cindy Lara Syarifah Putri (UIR Press, 2023)
The main objective of this research is to develop a Web-based online learning class platform for Accounting education students so that they can learn anywhere and anytime. The development design in this study uses the ADDIE model, which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. This product was tested on 20 Accounting education students class of 2019 in the introduction of the Pengantar Akuntansi 2 course. The results of data analysis show that students have the advantage of being able to immediately learn and know the extent of their understanding by taking a test after studying the material that has been shared. Through this platform students can learn material and evaluate the material they read anywhere and anytime. The convenience provided on this platform can increase the effectiveness and efficiency of learning in Accounting education